Investigation of micro-explosion phenomenon in the combustion of tri-fuel (diesel, biodiesel and bioethanol) emulsion in compression ignition engines - Hagos, Ftwi Yohaness; Rizalman, Mamat; Abdul Adam, Abdullah; Amir, Aziz; Omer, Ahmed Nurye; Abd. Rashid, Abd. Aziz (2015)
The current research is aimed at investigation the micro-explosion phenomenon of a tri-fuel emulsion in compression ignition (CI) engine. Alcohols and biodiesel to be emulsified in diesel fuel at different proportions for an improvement in the combustion, performance and emission through the manipulation of the microexplosion phenomenon. In its initial stage, the research planning was limited to preparation stage where the main activities in this stage are literature review and preparation of equipment and materials. Optimization of the ultrasonic emulsifier for the emulsion preparation by varying the amplitude, the pulse and time of emulsion has been conducted to see the effect of the stability of the emulsion. Besides, the stability and fuel characterization of different proportion of component fuels has been investigated and an article is in the review process. LAMPIRAN B Comparison between the emulsion and blending was studied. A setup for the spray characterization and compression ignition engine is ready. Onset of microexplosion phenomenon is investigated. The spray penetration comparison of different emulsified fuels and diesel fuel are compared. Besides, the spray spread, the droplet size, spray cone and spray dispersion and their relationship with the physico-chemical characteristics of the emulsified fuel is done. Flame visualization: Flame visualization has become a challenge on the progress of the study. The chamber is equipped with visualization window. the glass being used for the visualization is BK glass where it can only withstand temperature of 700 K. Therefore, the glass breaks when combustion is initiated. Therefore, the experiment is limited to spray characterization and investigation of microexplosion phenomenon. The combustion and emission study is completed. The effect of emulsification on the combustion, performance and emissions was investigated and their relationship with the physico-chemical characteristics of the emulsified fuel is done. The OPEN FOAM modeling, nozzle geometry is prepared, meshing is completed and setting up boundary and governing equations ongoing. The modeling work is completed. Model validation was done with the help of the experimental data. There is a strong agreement.